A FUZZY MULTIPLE ATTRIBUTE UTILITY MODEL FOR INTELLIGENT BUILDING ASSESSMENT - Kahraman, Cengiz; Kaya, Ihsan (VILNIUS GEDIMINAS TECH UNIV, 2012)
Multi-Attribute Utility Theory (MAUT) is an evaluation scheme which is very popular by decision makers for evaluating their judgments. According to MAUT, the overall evaluation U(x) of an object x is defined as a weighted addition of its evaluation with respect to its relevant value dimensions. The recent years have witnessed a huge concentration and interest in intelligent buildings' performance that is increasingly evidenced in building design and construction. Intelligent buildings (IBs) are also under assessment according to their IB related characteristics and actual circumstances. For this aim, in this paper a fuzzy multiple attribute utility model for intelligent building assessment is proposed and three alternative intelligent buildings for a business center in Istanbul are evaluated.
Keywords: Multiple attribute; utility model; fuzzy; decision making; intelligent building; assessment; RANKING; ALTERNATIVES; OPTIMIZATION; MANAGEMENT; SELECTION; NUMBERS; SYSTEMS; Engineering